The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jnatprod.1c00062
|View full text |Cite
|
Sign up to set email alerts
|

Gelstriamine A, a Triamino Monoterpene Indole Alkaloid with a Caged 6/5/7/6/6/5 Scaffold and Analgesic Alkaloids from Gelsemium elegans Stems

Abstract: A novel triamino monoterpene indole alkaloid with an unprecedented skeleton, gelstriamine A (1), four new monoterpene indole alkaloids (2−5), and 12 known analogues (6−17) were isolated from Gelsemium elegans. The structures of 1−5 were established using extensive spectroscopic techniques, NMR calculations with iJ/dJ-DP4 and 2D C−H COSY ANNs analysis, ECD calculations, chemical methods, and single crystal Xray diffraction analysis. Gelstriamine A (1) possesses an unprecedented 6/5/7/6/6/5 heterohexacyclic scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Furthermore, compound 205 is a novel triamino alkaloid with a novel 6/5/7/6/6/5 hetero hexacyclic ring system bearing a unique hexahydrooxazolo [4,5-b]pyridin-2(3 H )-one motif. In contrast, compound 208 is the first N -oxide of a sarpagine-type alkaloid isolated from a plant in the Gelsemium genus [ 58 ]. Compound 210 was isolated from the stems of Mostuea brunonis and is a novel sulfur-containing vobasine-type indole alkaloid.…”
Section: Isolation Of Novel Indole Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compound 205 is a novel triamino alkaloid with a novel 6/5/7/6/6/5 hetero hexacyclic ring system bearing a unique hexahydrooxazolo [4,5-b]pyridin-2(3 H )-one motif. In contrast, compound 208 is the first N -oxide of a sarpagine-type alkaloid isolated from a plant in the Gelsemium genus [ 58 ]. Compound 210 was isolated from the stems of Mostuea brunonis and is a novel sulfur-containing vobasine-type indole alkaloid.…”
Section: Isolation Of Novel Indole Alkaloidsmentioning
confidence: 99%
“…Moreover, compound 208 displayed lower activity than epi-koumidine and koumidine, inferring that the N 4 -oxide (not possessed by the latter two) decreased the activity of sarpagine-type alkaloids. Furthermore, compound 206 , 11-hydroxyhumantenine, and humantenirine contained a hydroxy or methoxy substituent at C-11and showed less potent activities, suggesting that these groups decreased the activities of humantenine-type alkaloids [ 58 ]. Compound 210 demonstrated no cytotoxicity against the MRC-5 cell line; however, it potently inhibited P. falciparum strain FcB1.…”
Section: Bioactivities Of Novel Indole Alkaloidsmentioning
confidence: 99%
“…(Loganiaceae), widely distributed in Southeast Asia, is known as a toxic plant and has been used as a traditional Chinese medicine for the treatment of eczema, carbuncle, and pain 5,6 . The alkaloids are the major components in the genus Gelsemium , and some of the alkaloids performed significant biological activities such as antitumor, 7 analgesic, 8 and anti‐inflammatory activities 9 . These alkaloids attracted the attentions of pharmacologists and chemists due to the structural features and multiple biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids are a kind of a nitrogen-containing alkalinous organic compound in nature (mainly in plants but also in animals ). Most of them have a complex ring structure containing nitrogen and exhibit significant biological activities. Alkaloids, as an important active component in Chinese herbal medicine, , play an important role in the treatment of Alzheimer’s disease (AD). , AD is an irreversible degenerative disease of the central nervous system. Its pathophysiological process includes degeneration of neurons and synapses and mainly cholinergic damage. , Some studies have shown that alkaloids can reduce the decomposition of acetylcholine (ACh) by inhibiting the activity of acetylcholinesterase (AChE) in vivo and alleviate the damage of AD to life ability and cognitive ability. …”
Section: Introductionmentioning
confidence: 99%